Programma: 2-29 januari: Dub War, Bintangs, Bentley Rhythm Ace, Laurel Aitken, Peter Hammill, Sugar Ray - Zero, (1998)
Programma: 2-29 januari: Dub War, Bintangs, Bentley Rhythm Ace, Laurel Aitken, Peter Hammill, Sugar Ray.